Effects of psychological factors on players’ performance with the mediation role of player’s satisfaction - Wenqiang Gao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Nowadays, most of the players from China are unable to perform outstandingly because of the effects of psychological factors which limit them and it is very common that these factors even don’t allow the players to perform accordingly. Hence, the primary objective of the current study is to investigate the role of psychological factors which affect a player’s performance particularly with the mediation role of the player’s satisfaction. To obtain the outcomes of the current study, a quantitative research approach was adopted. 760 football players who were the respondents of the current study were surveyed for the collection of primary data. Partial Least Square (PLS) was used to evaluate the final outcomes from the primary data. From the outcomes of the current study, it is obvious that a player’s psychological factors such as punctuality, mood, competition, and commitment have a positive effect on the player’s satisfaction and performance. The current study is helpful for the players particularly from China to boost their performances and satisfaction level. Moreover, the current study also helps the sports industry of China to increase players’ performances.